CORRELATION BETWEEN STUDENTS’ SELF ESTEEM AND ENGLISH LANGUAGE PROFICIENCY OF INDONESIAN EFL STUDENTS - Intan Satriani (STKIP Siliwangi, 2014)
The present research is employed to understand the relationship between self esteem and English language proficiency of Indonesian EFL students. The research was conducted on both Indonesian male and female graduate students of English department in a Postgraduate school in Bandung. During the research, questionnaire developed by Hyde (1979 in Bagheri, et al., 2012) was used as the research instrument to obtain the score of students’ self esteem. In addition, the data of English proficiency were collected from TOEFL score which has been standardized. Those instruments were administered in two sessions by one week interval. The data were analyzed by Pearson product moment correlation to identify the relationship between two variables. The result of this study showed that the students’ self esteem have significantly strong positive correlation with their language proficiency. Keywords: Self-Esteem, English language proficiency, Postgraduate students